ANALISIS PERSEPSI TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI PERUMAHAN VILLA GADING MAYANG DI KOTA JAMBI - Askar Veto Tremudya (Jurnal Dinamika Manajemen, 2013)
This research purpose is to analyze the relationship between consumer perceptions on poperty purchusing decsision of Villa Gading Mayang Jambi. Research sample is the owners that consists of 30 respondents. The analysis tool use ranking scale method on the consumer perceptions. Research results shows that the indicators considered to be the factor are prices influence consumer decisions and folowed by purchasing systems, environmental infrastructure, model / type of housing, quality of the home, the location of housing, and supporting facilities occupy the final sequence that gives the smallest index value. Hence, it is reccomend that the marketer consider factor that influece the consumer to buy poperty Keywords. Poperties, consumer perceptions, NGK, and biplot